PERANAN PEMBANGUNAN INFRASTRUKTUR DIGITAL DALAM GELIAT UMKM DI MASYARAKAT RW 10 DAN RW 11, DESA CIKARAGEMAN, KABUPATEN BEKASI, PROPINSI JAWA BARAT, MELALUI PEMANFAATAN MEDIA WHATSAPP - Aliardo, Mohammad (Jurnal Ilmu Administrasi Publik, 2025)
The government's policy through BAKTI Kominfo or the Ministry of Communication and Information's Telecommunication and Information Accessibility Agency in accelerating the development of digital infrastructure has encouraged a new economic model that utilizes social media. With the expansion of the internet network supported by the development of digital infrastructure in Indonesia, it allows for the use and utilization of the WhatsApp application as a marketing vehicle for home businesses and MSMEs. As done by the Community in RW 10 and RW 11, Cikarageman Village, Setu District, Bekasi Regency, West Java, who created a group in the WhatsApp application to market their products and goods and carry out buying and selling transactions.